Sc/SiC/Al Multilayer Optimization for Li K Spectroscopy - Khalil Hassebi; Evgueni Meltchakov; Franck Delmotte; Angelo Giglia; Philippe Jonnard (Applied Sciences, 2024)
This paper presents an X-ray reflectivity study of a Sc/SiC/Al periodic multilayer deposited via magnetron sputtering and its possible adaptation to be used as a dispersive element in the crystal spectrometers equipping scanning electron microscopes and electron probe microanalyzers. This multilayer is designed for the spectral range of 45–60 eV. The results reveal a reflectance of 40.8% at 54.1 eV for a near-normal incidence angle of 7° with a narrow bandwidth of 2.6 eV. The measured and simulated reflectivity curves are very close, suggesting that this system has smooth interfaces and low interdiffusion. Owing to the growing importance of lithium and lack of spectroscopic data, we simulate a new Sc/SiC/Al stack based on the reflectivity data and optimize it to perform spectroscopy in the range near the Li K absorption edge around 55 eV, which is in the spectral range of the Li Kα emission band. This optimization is achieved by tuning the thicknesses of the different layers and the number of periods of the multilayer using an in-house Python script. The optimization results are compared with the performances of other multilayers employed in the same energy range and at a working angle close to 30° grazing, including Be/Si/Al. This analysis indicates that the Sc/SiC/Al multilayer could be a good candidate for performing spectroscopy in the Li K range.